2007
DOI: 10.1254/jphs.fp0071371
|View full text |Cite
|
Sign up to set email alerts
|

Shengmai-san Enhances Antioxidant Potential in C2C12 Myoblasts Through the Induction of Intracellular Glutathione Peroxidase

Abstract: Abstract. Cellular and tissue injury associated with reactive oxygen species (ROS) has been reported in many kinds of disorders. While the antioxidant enzymes play critical roles in inhibiting the ROS-mediated injury, glutathione peroxidase (GPx) is scavenging hydroperoxides including H 2 O 2 . We previously reported that Shengmai-san (SMS), a traditional Chinese medicine, prevented ischemia / reperfusion injury of the brain and other organs in rats. To clarify the effect of SMS on intracellular responses of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…[4][5][6] Cell injury associated with ROS may contribute to a variety of muscle diseases and pathologic conditions. 29) To clarify the effect of sauchinone on the oxidative stress response in muscle cells, we exposed C 2 C 12 skeletal muscle myoblasts to H 2 O 2 .…”
Section: Measurement Of Ceramide Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Cell injury associated with ROS may contribute to a variety of muscle diseases and pathologic conditions. 29) To clarify the effect of sauchinone on the oxidative stress response in muscle cells, we exposed C 2 C 12 skeletal muscle myoblasts to H 2 O 2 .…”
Section: Measurement Of Ceramide Contentmentioning
confidence: 99%
“…1,2) Skeletal muscle cells are susceptible to oxidative stress induced through electron transport and oxygen flux during normal contraction, and this stress may increase with exercise intensity. [1][2][3][4][5][6] Muscle redox status, especially during atrophy, is more oxidative than the redox status in other organs. Augmentation of cellular antioxidant defense presents a basic strategy for controlling oxidative muscle injury and related disease conditions.…”
mentioning
confidence: 99%
“…It was shown that α-tocopherol treatment improved neurite outgrowth of cultured retinal ganglion cells (35). Having noted that the protective effects of SMS on oxidative damages in different kind of cells or tissues might be shared mechanistically with those of α-tocopherol, several studies reported similar protection by α-tocopherol (14,16,36,37). Our data showed that neurite outgrowth of DRG sensory neurons was enhanced to a similar level by treatment of either SMS or α-tocopherol in comparison to the untreated control, which implicates physiological significance of the antioxidant activity of SMS for axonal regeneration.…”
Section: Discussionmentioning
confidence: 97%
“…[23][24][25][26] Skeletal muscle cells and myoblasts are susceptible to oxidative stress induced through electron transport and oxygen flux during normal contraction, and this stress may increase with exercise intensity. [1][2][3][4][5][6] Augmentation of cellular antioxidant defense presents a basic strategy to control oxidative muscle injury and related disease conditions. The present study demonstrates the potential benefits of herbal medicines in treating oxidative stress-related muscle disorders.…”
Section: Discussionmentioning
confidence: 99%